Pengembangan Usaha Keripik Tempe melalui Kolaborasi Lembaga Manajemen Infaq dan YBM PLN dalam Program Pemberdayaan Masyarakat di Kelurahan Keniten - Dyah Ayu Fatmawati; Aufa Izzuddin Baihaqi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Community empowerment programs play an important role in improving community welfare and economic empowerment. One form of this program is the collaboration between LMI and YBM PLN to develop a tempeh chips business in Keniten Village. The purpose of this research is to analyze the results and impact of community empowerment programs. This research was conducted using field research methods or field research. The results of the research show that this community empowerment program has succeeded in providing significant social and economic impacts for the people of Keniten Village. The community experienced an increase in income and economic welfare from the tempeh chips business. As a result, recommendations are made to expand market access, improve technicalities- develop more effective marketing strategies. In conclusion, the collaboration between LMI and YBM PLN in the community empowerment program in Keniten Village has had a positive impact on the development of the tempeh chips business and economic community empowerment.